Near-infrared second-zone life-enhanced long afterglow / carbon dot composite nanomaterial, preparation method and application

By combining long afterglow nanomaterials with carbon quantum dots, a composite nanomaterial with enhanced lifetime in the near infrared region was solved, and the emission wavelength limitations of the existing technology of long afterglow nanomaterials and phototoxicity of organisms was achieved, and the near infrared was achieved The luminescence intensity of zone 2 is enhanced and the bioimaging depth is improved.

CN119490849APending Publication Date: 2025-02-21喀什大学
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556590.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The emission wavelength of existing long afterglow nanomaterials in biological imaging is limited to the near-infrared region, resulting in limited penetration depth and phototoxicity to organisms, making it difficult to achieve deep penetration and long-term repeated biological imaging.

Method used

Develop a long afterglow/carbon dot composite material with enhanced lifetime in the near-infrared second zone. By combining long afterglow nanomaterials with carbon quantum dots through covalent bonding, a kind of in-situ excitation, easy surface functionalization, and good fluorescence is constructed The composite nanomaterial with performance uses carbon quantum dots luminous in the visible light region to transmit energy to the long afterglow nanomaterial luminous in the near infrared second region, enhancing its luminous intensity in the near infrared second region.

Benefits of technology

The luminescence intensity enhancement in the second zone of near infrared is achieved, the luminescence life is extended, the depth and sensitivity of biological imaging are improved, the phototoxicity to organisms is reduced, and the application prospects of biological imaging are broad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490849A_ABST
    Figure CN119490849A_ABST
Patent Text Reader

Abstract

The invention relates to a long-afterglow / carbon dot composite nanomaterial with the service life of a near-infrared second zone enhanced, a preparation method and application, the composite nanomaterial is formed by combining a long-afterglow nanomaterial and carbon quantum dots CDs through covalent bonds, the preparation method comprises the steps that the long-afterglow nanomaterial PLNPs is subjected to surface functionalization, and the long-afterglow / carbon dot composite nanomaterial with the service life of the near-infrared second zone enhanced is obtained. Energy level matching of the PLNPs and the CDs is achieved, and therefore energy transfer between the two materials is enhanced. Under the irradiation of 254nm light, the CDs can emit strong green light, energy is transferred to the PLNPs through the CDs, so that the light emission of the PLNPs in a near-infrared second region is enhanced, and after an excitation light source is turned off, the composite nano material continuously emits light in the near-infrared second region through energy transfer, so that the light emission of the PLNPs in the near-infrared second region is enhanced. A new application and future application expansion are provided for near-infrared two-region biological imaging without in-situ excitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application mainly belongs to the technical field of preparation of luminescent materials, and in particular relates to a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region, a preparation method of a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, and an application of a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region. Background Art

[0002] Long afterglow material is a light-storing luminescent material. After the excitation of the excitation light source (mostly X-rays, ultraviolet light or visible light) stops, the afterglow of the long afterglow material can continue to emit light. Its special optical properties enable it to achieve long afterglow luminescence without in-situ excitation after pre-excitation by an external light source. Therefore, it can avoid the interference of the organism's own background fluorescence and the light damage caused by continuous irradiation to the greatest extent, and achieve highly sensitive biological optical imaging.

[0003] The second near-infrared window NIR-II (1000nm-1700nm) can achieve high temporal and spatial resolution and high-depth imaging of living bodies due to its small photon scattering and weak autofluorescence, and has become a hot topic in biomedical research.

[0004] Composite materials of near-infrared long-lasting nanomaterials (NIR-PLNPs) combined with quantum dots are a new type of nanomaterial with great application prospects because of their unique luminescence properties. They can emit light continuously for a short period of time and are not affected by the spontaneous fluorescence of biological tissues. However, the emission wavelength of this type of composite material is currently limited to the near-infrared region (700nm-1000nm), and a single material will cause stronger phototoxicity and scattering to organisms in biological imaging, resulting in limited penetration depth. Therefore, the inability to achieve deep penetration and long-term repeated biological imaging is a major challenge in the current application and development of long-lasting nanomaterials. Summary of the invention

[0005] In view of this, the development of long afterglow / carbon dot composite materials with enhanced lifetime in the second near-infrared region is of great significance and broad application prospects. The present application aims to provide a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, a preparation method and related applications.

[0006] The first aspect of the present application provides a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, wherein the long afterglow / carbon dot composite nanomaterial is PLNPs-CDs, and the chemical formula is (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs, where 1≤x≤7, 1≤y≤7.

[0007] In some embodiments of the present application, chemical formula (x) Zn3Ga2Ge2O 10:The mass fraction ratio of Mn,Ho-(y)CDs is x:y=7:1.

[0008] The second aspect of the present application provides a method for preparing a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, the preparation method specifically comprising: 2+ Ion solution, Ga 3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ The ion solution and ethylene glycol are mixed, stirred evenly at room temperature and the pH value is adjusted to 6-8 to obtain a mixed solution of the ion solution, and the reaction is continued at 160°C to 170°C for 12h to 15h. After the reaction is completed, a series of post-treatment operations are performed to obtain a white solid. The white solid is fully ground and calcined at 800°C to 1000°C to obtain Zn3Ga2Ge2O 10 :Mn,Ho long afterglow nanomaterials; different mass percentage concentrations of safranine T (ST) and NaOH solution are mixed to obtain a mixed solution, and after the ST in the mixed solution is completely dissolved, it is heated at 190℃~210℃ for 4h-6h, and after the reaction is completed, it is cooled to room temperature to obtain a CDs-COOH aqueous solution, that is, a carbon quantum dot CDs with a carboxyl-COOH functional group on the surface and different emission wavelengths is obtained, which is stored at 3℃~5℃ for standby use; Zn3Ga2Ge2O 10 :Mn,Ho long afterglow nanomaterials are dispersed in NaOH solution and fully mixed to obtain hydroxylated long afterglow nanomaterial PLNPs-OH; PLNPs-OH is dispersed in DMF, y-aminopropyltriethoxysilane (APTES) is added, and the mixture is fully mixed at 70°C to 90°C to obtain amino-modified long afterglow nanomaterial PLNPs-NH2; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to CDs-COOH aqueous solution, and the mixture is fully stirred under light-proof conditions; PLNPs-NH2 is added and fully mixed to obtain (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs composite nanomaterials, (x)Zn3Ga2Ge2O 10 :In Mn,Ho-(y)CDs, the values ​​of x and y are 1≤x≤7 and 1≤y≤7 respectively.

[0009] In some embodiments of the present application, in the step of obtaining a mixed solution of ionic solution, according to Zn 2+ :Ga 3+ :Ge 4 + :Mn 2+ :Ho 3+= Zn added in a molar ratio of 0.3:0.2:0.2:0.05:0.08 2+ Ion solution, Ga 3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ Ionic solution.

[0010] In some embodiments of the present application, in the step of obtaining a mixed solution of ionic solution, stirring is performed at room temperature for 20 min-40 min, the pH value is adjusted to 6-8 with ammonia water with a mass concentration of 5%-15%, and stirring is continued at room temperature for 1 h-2 h to obtain a mixed solution of ionic solution.

[0011] In some embodiments of the present application, the step of obtaining a mixed solution of ionic solutions includes at least one of the following: Zn 2+ The ionic solution is prepared by dissolving an appropriate amount of ZnCl2 in concentrated HCl. 2+ The concentration is 0.8 mol / L; Ga 3+ The ion solution was prepared by dissolving an appropriate amount of Ga(NO3)3·xH2O in deionized water. 3+ The concentration is 0.2 mol / L; Ge 4+ The ion solution is prepared by dissolving an appropriate amount of GeO2 in dilute NH3·H2O. 4+ The concentration is 0.2 mol / L; Mn 2+ The ion solution was prepared by dissolving an appropriate amount of MnCl2·4H2O in deionized water. 2+ The concentration is 0.01 mol / L; Ho 3+ The ion solution was prepared by dissolving an appropriate amount of Ho(NO3)3·5H2O in deionized water. 3+ The concentration is 0.01mol / L.

[0012] In some embodiments of the present application, in the step of obtaining a white solid, the post-processing operation includes: the mixed solution of the ionic solution is naturally cooled to room temperature after the reaction is completed at a temperature of 160°C to 170°C, centrifuged, washed several times with anhydrous ethanol and deionized water in sequence, and dried at a temperature of 60°C to 80°C under a vacuum environment to obtain a white solid.

[0013] In some embodiments of the present application, in the step of obtaining the CDs-COOH aqueous solution, the mass percentage concentration of safranin T (ST) includes at least one of the following: 0.7%, 1%, 1.67%, 5%, 15%, 25%, 35%.

[0014] In some embodiments of the present application, when (x) Zn3Ga2Ge2O is obtained 10: The step of preparing Mn,Ho-(y)CDs composite nanomaterials includes at least one of the following: the mass ratio of CDs-COOH aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and N-hydroxysuccinimide is 10:5:7; the mass ratio of CDs-COOH aqueous solution and PLNPs-NH2 is 1-7:1-7, and the preferred mass ratios are 1:7, 1:5, 1:3, 1:1, 3:1, 5:1, and 7:1.

[0015] The third aspect of the present application provides an application of a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, which is applied in the field of biological imaging, including at least nanoprobes and biological detection.

[0016] Beneficial effects of this application:

[0017] (1) The present application relates to a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region: the long afterglow nanomaterial is a photoluminescent material that emits visible light when excited by a light source and stores part of the obtained light energy. After the excitation stops, the energy is slowly released in the form of light; carbon quantum dots CDs are a zero-dimensional carbon material with a size less than 10 nm, which has many advantages such as excellent optical properties, good water solubility, low toxicity, environmental friendliness, wide source of raw materials, low cost, and good biocompatibility; the long afterglow / carbon dot composite material of the present application combines the long afterglow nanomaterial with carbon quantum dots through covalent bonds, successfully constructing a composite nanomaterial with enhanced lifetime in the second near-infrared region that is free of in-situ excitation, easy to surface functionalize, has good fluorescence properties, and has good biocompatibility. The material uses carbon quantum dots that emit light in the visible light region to transfer energy to the long afterglow nanomaterial that emits light in the second near-infrared region, thereby enhancing its luminescence intensity in the second near-infrared region.

[0018] (2) The present application relates to a method for preparing a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region: the preparation method is simple, efficient, and has low raw material prices, which is conducive to the widespread preparation and application of long afterglow / carbon dot composite materials.

[0019] (3) The present application relates to the application of a long afterglow / carbon dot composite material with enhanced lifetime in the near-infrared zone II. The long afterglow / carbon dot composite material PLNPs-CDs has good biocompatibility and water solubility on the one hand, and can obtain near-infrared zone II luminescence without in situ excitation through short-wavelength 254nm ultraviolet light irradiation, which has good application prospects in biological imaging. In addition, the composite nanomaterial has good fluorescence properties and can be suitable for biological imaging of deeper tissues, which can provide a new method for near-infrared zone II biological imaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings.

[0021] Figure 1 This is a transmission electron microscope image of the composite nanomaterial PLNPs-CDs of this application;

[0022] Figure 2 This is the excitation-emission spectrum of the composite nanomaterial PLNPs-CDs of this application;

[0023] Figure 3 This is the luminescence lifetime spectrum of the long afterglow nanomaterial PLNPs and the composite nanomaterial PLNPs-CDs of this application. DETAILED DESCRIPTION

[0024] In order to make the application purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0025] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0026] The first aspect of the present application provides a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, wherein the long afterglow / carbon dot composite nanomaterial is PLNPs-CDs, and the chemical formula is (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs, where the mass fraction ratio ranges from 1≤x≤7 to 1≤y≤7.

[0027] In some embodiments of the present application, chemical formula (x) Zn3Ga2Ge2O 10 :The mass fraction ratio in Mn,Ho-(y)CDs is x:y=7:1.

[0028] The second aspect of the present application provides a method for preparing a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, the preparation method specifically comprising:

[0029] S1, Zn 2+ Ion solution, Ga 3+Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ The ion solution and ethylene glycol are mixed in a container, stirred at room temperature for 20 minutes to 40 minutes until the mixture is uniformly stirred, the pH value is adjusted to 6-8 with ammonia water with a mass concentration of 5% to 15%, and the mixture is stirred at room temperature for 1 hour to 2 hours to obtain a mixed solution of the ion solution; the mixed solution is poured into a polytetrafluoroethylene-lined reactor, and the reaction is continued at a temperature of 160° C. to 170° C. for 12 hours to 15 hours. After the reaction is completed, a series of post-treatment operations are performed to obtain a white solid, the white solid is fully ground, and then transferred to a muffle furnace and calcined at a temperature of 800° C. to 1000° C. for 2 hours to 4 hours to obtain Zn3Ga2Ge2O 10 :Mn,Ho long afterglow nanomaterials;

[0030] S2. Safflower T (ST) with different mass percentage concentrations and NaOH solution are mixed in clean beakers to obtain a mixed solution, and the ST in the mixed solution is completely dissolved by ultrasonic treatment for 5min-15min. The mixed solution with ST fully dissolved is transferred to a polyethylene-lined autoclave, and heated at 190℃~210℃ for 4h-6h. After the reaction is completed, it is naturally cooled to room temperature to obtain a CDs-COOH aqueous solution, that is, carbon quantum dots CDs with carboxyl-COOH functional groups on the surface and different emission wavelengths are obtained, which are stored in a refrigerator at 3℃~5℃ for future use;

[0031] S3, Zn3Ga2Ge2O 10 : Mn, Ho long afterglow nanomaterials are dispersed in NaOH solution and fully mixed, stirred overnight to obtain hydroxylated long afterglow nanomaterial PLNPs-OH, PLNPs-OH is dispersed in DMF, y-aminopropyltriethoxysilane (APTES) is added, and the mixture is fully mixed and stirred overnight at 70°C to 90°C to obtain aminolated long afterglow nanomaterial PLNPs-NH2;

[0032] S4, add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to the CDs-COOH aqueous solution, stir thoroughly under light-proof conditions, add PLNPs-NH2 and mix thoroughly to obtain (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs composite nanomaterials, in which (x)Zn3Ga2Ge2O 10 :In Mn,Ho-(y)CDs, the values ​​of x and y are 1≤x≤7 and 1≤y≤7 respectively.

[0033] In some embodiments of the present application, in step S1, Zn 2+ Ion solution, Ga3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ The molar ratio of the added amount of ion solution is Zn 2+ :Ga 3+ :Ge 4+ :Mn 2+ :Ho 3+ =0.3:0.2:0.2:0.05:0.08.

[0034] In some embodiments of the present application, in step S1, at least one of the following is included:

[0035] Zn 2+ The ionic solution is prepared by dissolving an appropriate amount of ZnCl2 in concentrated HCl. 2+ The concentration is 0.8 mol / L;

[0036] Ga 3+ The ion solution was prepared by dissolving an appropriate amount of Ga(NO3)3·xH2O in deionized water. 3+ The concentration is 0.2 mol / L;

[0037] Ge 4+ The ion solution is prepared by dissolving an appropriate amount of GeO2 in concentrated NH3·H2O. 4+ The concentration is 0.2 mol / L;

[0038] Mn 2+ The ion solution was prepared by dissolving an appropriate amount of MnCl2·4H2O in deionized water. 2+ The concentration is 0.01 mol / L;

[0039] Ho 3+ The ion solution was prepared by dissolving an appropriate amount of Ho(NO3)3·5H2O in deionized water. 3+ The concentration is 0.01mol / L.

[0040] In some embodiments of the present application, in step S1, in the operation of obtaining a white solid, the post-treatment operation of the mixed solution of the ionic solution that continuously reacts at a temperature of 160°C to 170°C includes: naturally cooling the mixed solution of the ionic solution to room temperature after the reaction is completed at a temperature of 160°C to 170°C, separating the solid and the liquid by centrifugation, washing the solid collected by centrifugation with anhydrous ethanol and deionized water for several times in turn, and drying it at a temperature of 60°C to 80°C under a vacuum environment to obtain a white solid.

[0041] In some embodiments of the present application, in step S2, in the operation of obtaining the CDs-COOH aqueous solution, the mass percentage concentration of safranin T (ST) includes at least one of the following: 0.7%, 1%, 1.67%, 5%, 15%, 25%, 35%.

[0042] In some embodiments of the present application, in step S3, in the operation of obtaining the composite nanomaterial, PLNPs-OH can be dispersed in DMF by ultrasound.

[0043] In some embodiments of the present application, in step S3, the composite nanomaterial (x) Zn3Ga2Ge2O is obtained. 10 : The operation of Mn,Ho-(y)CDs includes at least one of the following:

[0044] The mass ratio of CDs-COOH aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and N-hydroxysuccinimide was 10:5:7;

[0045] The mass ratio of CDs-COOH aqueous solution and PLNPs-NH2 is 1-7:1-7, and the preferred mass ratio is 1:7, 1:5, 1:3, 1:1, 3:1, 5:1, and 7:1. In different embodiments, by adjusting the mass fraction ratio of PLNPs-NH2 and CDs, long afterglow / carbon dot composite nanomaterials with enhanced lifetime in the second near-infrared region of different proportions can be prepared, including but not limited to PLNPs-CDs (7:1), PLNPs-CDs (5:1), PLNPs-CDs (3:1), PLNPs-CDs (1:1), PLNPs-CDs (1:3), PLNPs-CDs (1:5) and PLNPs-CDs (1:7).

[0046] In some embodiments of the present application, in step S3, the composite nanomaterial (x) Zn3Ga2Ge2O is obtained. 10 : In the operation of Mn,Ho-(y)CDs, the stirring time under light-proof conditions is 1h-3h.

[0047] The third aspect of the present application provides an application of a long afterglow / carbon dot composite material with enhanced lifetime in the second near-infrared region, which is applied in the field of biological imaging, including at least nanoprobes and biological detection.

[0048] The present application will be described in further detail below in conjunction with specific exemplary embodiments. It should be understood that the specific embodiments described herein are intended only to explain the present application, rather than to limit the present application. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0049] Example 1

[0050] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The composite nanomaterial is PLNPs-CDs, and the preparation method includes the following steps:

[0051] S1. Preparation of long afterglow nanomaterials

[0052] Take an appropriate amount of Ga(NO3)3·xH2O and dissolve it in deionized water to prepare a Ga(NO3)3·xH2O solution with a concentration of 0.2 mol / L. 3+ Solution; Take an appropriate amount of GeO2 and dissolve it in concentrated NH3·H2O to prepare GeO2 with a concentration of 0.2 mol / L. 4+ Solution; Take an appropriate amount of Ho(NO3)3·5H2O and dissolve it in deionized water to prepare a 0.01 mol / L solution of Ho 3+ Solution; Take an appropriate amount of MnCl2·4H2O and dissolve it in deionized water to prepare a Mn solution with a concentration of 0.01 mol / L. 2+ Solution; Take an appropriate amount of ZnCl2 and dissolve it in concentrated HCl to prepare a Zn solution with a concentration of 0.8 mol / L. 2+ Solution; According to Zn 2 + :Ga 3+ :Ge 4+ :Mn 2+ :Ho 3+ =0.3:0.2:0.2:0.05:0.08 molar ratio of Zn 2+ Ion solution, Ga 3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution and Ho 3+ The ion solution and ethylene glycol are mixed in a container, stirred at room temperature for 30 minutes, and then the pH value of the mixed solution is adjusted to 7 with ammonia water with a mass concentration of 10%, and the stirring is continued at room temperature for 1 hour to obtain a mixed solution of the ion solution; the obtained mixed solution of the ion solution is poured into a polytetrafluoroethylene-lined reactor, maintained at 170° C. for 14 hours, and naturally cooled to room temperature after the reaction is completed. After centrifugation, it is washed several times with anhydrous ethanol and deionized water respectively, and dried at 70° C. in vacuum to obtain a white solid; the above white solid is fully ground and transferred to a muffle furnace, and calcined at 950° C. for 3 hours to obtain Zn3Ga2Ge2O 10 :Mn,Ho long afterglow nanomaterials.

[0053] S2. Preparation of carbon quantum dots

[0054] A 35% mass percent concentration of safranin T (ST) and a NaOH solution were mixed in a beaker and subjected to ultrasonic treatment for 10 minutes to completely dissolve ST to obtain a mixed solution, and then the mixed solution was transferred to a polyethylene-lined autoclave and heated at 200° C. for 5 hours to obtain a CDs-COOH aqueous solution, i.e., carbon quantum dots CDs containing a -COOH functional group, which were naturally cooled to room temperature and then stored in a refrigerator at 4° C. for future use;

[0055] S3. Surface functionalization of long afterglow nanomaterials

[0056] Weigh 400 mg of the long afterglow nanomaterial obtained in step S1 and disperse it in 100 ml of a 5 mmol / L NaOH solution, and stir overnight to obtain a hydroxylated long afterglow nanomaterial PLNPs-OH; then weigh 100 mg of PLNPs-OH and ultrasonically disperse it in 40 ml of DMF, then add 400 ul of y-aminopropyltriethoxysilane (APTES), and stir overnight at 80°C to obtain an amino-containing long afterglow nanomaterial PLNPs-NH2.

[0057] S4. Preparation of composite nanomaterials

[0058] To 100 mg of carboxylated carbon quantum dots, 50 mg of 1-ethyl (3-dimethylaminopropyl) -3-ethylcarbodiimide hydrochloride and 70 mg of N-hydroxysuccinimide were added and stirred for 2 h in a dark environment. Then, a certain amount of amino-containing long afterglow nanomaterial PLNPs-NH2 was mixed and stirred for 48 h to obtain a PLNPs-CDs composite nanomaterial. The mass fraction ratio of x and y was x = 7 and y = 1, and the composite nanomaterial PLNPs-CDs (7:1) was obtained.

[0059] Example 2

[0060] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the high-temperature calcination time in step S1 is 3 hours.

[0061] Example 3

[0062] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the high-temperature calcination temperature in step S1 is 950°C.

[0063] Example 4

[0064] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=5, y=1, and the prepared composite nanomaterial is PLNPs-CDs (5:1).

[0065] Example 5

[0066] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=3, y=1, and the prepared composite nanomaterial is PLNPs-CDs (3:1).

[0067] Example 6

[0068] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=1, y=1, and the prepared composite nanomaterial is PLNPs-CDs (1:1).

[0069] Example 7

[0070] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=1, y=3, and the prepared composite nanomaterial is PLNPs-CDs (1:3).

[0071] Example 8

[0072] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=1, y=5, and the prepared composite nanomaterial is PLNPs-CDs (1:5).

[0073] Example 9

[0074] This embodiment provides a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region and a preparation method. The preparation method is basically the same as that in Example 1, except that the values ​​of x and y in step S4 are x=1, y=7, and the prepared composite nanomaterial is PLNPs-CDs (1:7).

[0075] Test Example 1

[0076] The composite nanomaterials prepared in Example 1 and Examples 4-9 were sampled and subjected to high-resolution transmission electron microscopy tests according to the Hitachi HT7820 general test standard. The test results are as follows: Figure 1 shown.

[0077] Figure 1 This is the transmission electron microscopy image of the composite nanomaterial PLNPs-CDs. From the image, it can be observed that CDs are wrapped on the surface of PLNPs, indicating the successful synthesis of the composite nanomaterial.

[0078] Test Example 2

[0079] The composite nanomaterials prepared in Example 1 and Examples 4-9 were sampled and subjected to steady-state spectrum test according to the FS5C steady-state transient spectrum universal test standard. The test results are as follows: Figure 2 shown.

[0080] Figure 2 This is the excitation-emission spectrum of the composite nanomaterial PLNPs-CDs. It can be seen from the figure that the luminescence intensity of the composite nanomaterials with different proportions increases with the increase of the PLNPs proportion. Therefore, the light emitted by CDs can be absorbed and utilized by PLNPs through the energy transfer mechanism.

[0081] Test Example 3

[0082] The composite nanomaterials prepared in Example 1 and Examples 4-9 were sampled and subjected to a long life test according to the FS5C steady-state transient spectrum universal test standard. The test results are as follows: Figure 3 shown.

[0083] Figure 3 The luminescence lifetime spectra of the composite nanomaterials PLNPs-CDs and pure long afterglow nanomaterials PLNPs under 254nm laser excitation: Under the same test conditions, we studied the luminescence lifetime intensity of pure PLNPs and composite nanomaterials with different proportions of PLNPs-CDs (7:1), PLNPs-CDs (5:1), PLNPs-CDs (3:1), PLNPs-CDs (1:1), PLNPs-CDs (1:3), PLNPs-CDs (1:5) and PLNPs-CDs (1:7). It can be found from the figure that the lifetime of PLNPs-CDs is greater than that of pure PLNPs, and the luminescence lifetime intensity of PLNPs-CDs7:1) is the best, which proves that after pure PLNPs combine with CDs, the lifetime of the composite nanomaterial is enhanced through the energy transfer mechanism.

[0084] It should be noted that, in addition to the cases listed in Examples 1 to 9 above, it is also feasible to select other raw material ratios and preparation method parameters.

[0085] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region, characterized in that: The long afterglow / carbon dot composite nanomaterial is PLNPs-CDs, and the chemical formula is (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs, where 1≤x≤7, 1≤y≤7.

2. The long afterglow / carbon dot composite nanomaterial according to claim 1, characterized in that: The chemical formula (x) is Zn3Ga2Ge2O 10 :The mass fraction ratio of Mn,Ho-(y)CDs is x:y=7:

1.

3. A method for preparing the long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region as claimed in claim 1 or 2, characterized in that: The preparation method comprises: Zn 2+ Ion solution, Ga 3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ The ion solution and ethylene glycol are mixed, stirred evenly at room temperature and the pH value is adjusted to 6-8 to obtain a mixed solution of the ion solution, and the reaction is continued at a temperature of 160° C. to 170° C. for 12 h to 15 h. After the reaction is completed, a series of post-treatment operations are performed to obtain a white solid. The white solid is fully ground and calcined at a temperature of 800° C. to 1000° C. to obtain Zn3Ga2Ge2O 10 :Mn,Ho long afterglow nanomaterials; The safranin T (ST) with different mass percentage concentrations was mixed with the NaOH solution to obtain a mixed solution. After the ST in the mixed solution was completely dissolved, it was heated at 190°C to 210°C for 4h-6h. After the reaction was completed, it was cooled to room temperature to obtain a CDs-COOH aqueous solution, that is, carbon quantum dots CDs with carboxyl-COOH functional groups on the surface and different emission wavelengths were obtained, and the mixture was stored at 3°C ​​to 5°C for future use; The Zn3Ga2Ge2O 10 : Mn, Ho long afterglow nanomaterials are dispersed in NaOH solution and fully mixed to obtain hydroxylated long afterglow nanomaterial PLNPs-OH, the PLNPs-OH is dispersed in DMF, y-aminopropyltriethoxysilane (APTES) is added, and the mixture is fully mixed at 70° C. to 90° C. to obtain aminolated long afterglow nanomaterial PLNPs-NH2; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added to the CDs-COOH aqueous solution, stirred thoroughly under light-proof conditions, and the PLNPs-NH2 was added and mixed thoroughly to obtain (x)Zn3Ga2Ge2O 10 :Mn,Ho-(y)CDs composite nanomaterials, the (x)Zn3Ga2Ge2O 10 :In Mn,Ho-(y)CDs, the values ​​of x and y are 1≤x≤7 and 1≤y≤7 respectively.

4. The preparation method according to claim 3, characterized in that: In the step of obtaining the mixed solution of the ion solution, according to Zn 2+ :Ga 3+ :Ge 4+ :Mn 2+ :Ho 3+ = Zn added in a molar ratio of 0.3:0.2:0.2:0.05:0.08 2+ Ion solution, Ga 3+ Ionic solution, Ge 4+ Ionic solution, Mn 2+ Ionic solution, Ho 3+ Ionic solution.

5. The preparation method according to claim 3, characterized in that: In the step of obtaining the mixed solution of the ion solution, stirring is performed at room temperature for 20 min-40 min, the pH value is adjusted to 6-8 with ammonia water having a mass concentration of 5%-15%, and stirring is continued at room temperature for 1 h-2 h to obtain the mixed solution of the ion solution.

6. The preparation method according to claim 4 or 5, characterized in that: The step of obtaining the mixed solution of the ion solution comprises at least one of the following: The Zn 2+ The ionic solution is prepared by dissolving an appropriate amount of ZnCl2 in concentrated HCl. 2+ The concentration is 0.8 mol / L; The Ga 3+ The ion solution was prepared by dissolving an appropriate amount of Ga(NO3)3·xH2O in deionized water. 3+ The concentration is 0.2 mol / L; The Ge 4+ The ion solution is prepared by dissolving an appropriate amount of GeO2 in concentrated NH3·H2O. 4+ The concentration is 0.2 mol / L; The Mn 2+ The ion solution was prepared by dissolving an appropriate amount of MnCl2·4H2O in deionized water. 2+ The concentration is 0.01 mol / L; The Ho 3+ The ion solution was prepared by dissolving an appropriate amount of Ho(NO3)3·5H2O in deionized water. 3+ The concentration is 0.01mol / L.

7. The preparation method according to claim 6, characterized in that: In the step of obtaining the white solid, the post-treatment operation includes: after the reaction of the mixed solution of the ion solution at a temperature of 160°C to 170°C is completed, it is naturally cooled to room temperature, centrifuged, washed several times with anhydrous ethanol and deionized water in sequence, and dried at a temperature of 60°C to 80°C under a vacuum environment to obtain the white solid.

8. The preparation method according to claim 3, characterized in that: In the step of obtaining the CDs-COOH aqueous solution, the mass percentage concentration of the safranin T (ST) includes at least one of the following: 0.7%, 1%, 1.67%, 5%, 15%, 25%, and 35%.

9. The preparation method according to claim 3, characterized in that: In the above method, (x)Zn3Ga2Ge2O 10 : The step of preparing the Mn, Ho-(y)CDs composite nanomaterial comprises at least one of the following: The mass ratio of the CDs-COOH aqueous solution, the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and the N-hydroxysuccinimide is 10:5:7; The mass ratio of the CDs-COOH aqueous solution to the PLNPs-NH2 is 1-7:1-7, and the preferred mass ratios are 1:7, 1:5, 1:3, 1:1, 3:1, 5:1, and 7:

1.

10. An application of a long afterglow / carbon dot composite nanomaterial with enhanced lifetime in the second near-infrared region as claimed in claim 1 or 2, wherein the long afterglow / carbon dot composite nanomaterial is prepared according to the preparation method according to any one of claims 3 to 8, characterized in that: Applications in the field of biological imaging include at least nanoprobes and biological detection.